2018
DOI: 10.1371/journal.pone.0191475
|View full text |Cite
|
Sign up to set email alerts
|

ERP evidence for consumer evaluation of copycat brands

Abstract: Copycat brands mimic brand leaders to free ride on the latter's equity. However, little is known regarding if and how consumers confuse copycat as leading brand in purchasing. In this study, we applied a word-pair evaluation paradigm in which the first word was a brand name (copycat vs. normal brand both similar with a leading brand in category), followed by a product name (near vs. far from the leading brand’s category). Behavioral results showed that, when the product is near the leader’s category, the copyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Based on the grand average waveforms (Figure 3, panel A), the scalp topography (Figure 3 panel B), as well as previous research on decision-making (Chen et al, 2010b; Gunter et al, 1994; Wang et al, 2016), two ERP components, N400, and LPP, were analyzed in this study. Six electrodes (F3, FZ, F4, FC3, FCZ, and FC4) distributed from the frontal to frontal-central regions were selected for N400 analysis (Gunter et al, 1994; Wang et al, 2016), and nine electrodes (C3, CZ, C4, CP3, CPZ, CP4, P3, PZ, and P4) distributed from the central to parietal regions were selected for LPP analysis (Fu et al, 2019; Shang et al, 2018). The mean amplitude of N400 in the time window of 380–480 ms was submitted to a 2 (review’s mobile phone price: high price and low price) × 6 (electrodes: F3, FZ, F4, FC3, FCZ, and FC4) repeated-measure ANOVA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the grand average waveforms (Figure 3, panel A), the scalp topography (Figure 3 panel B), as well as previous research on decision-making (Chen et al, 2010b; Gunter et al, 1994; Wang et al, 2016), two ERP components, N400, and LPP, were analyzed in this study. Six electrodes (F3, FZ, F4, FC3, FCZ, and FC4) distributed from the frontal to frontal-central regions were selected for N400 analysis (Gunter et al, 1994; Wang et al, 2016), and nine electrodes (C3, CZ, C4, CP3, CPZ, CP4, P3, PZ, and P4) distributed from the central to parietal regions were selected for LPP analysis (Fu et al, 2019; Shang et al, 2018). The mean amplitude of N400 in the time window of 380–480 ms was submitted to a 2 (review’s mobile phone price: high price and low price) × 6 (electrodes: F3, FZ, F4, FC3, FCZ, and FC4) repeated-measure ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…The N400 is a negative deflection that typically peaks around 400 ms poststimulus presentation (Chen et al, 2010a; Gunter et al, 1994). N400 is usually distributed from the frontal to the parietal scalp regions and its amplitude was larger in the frontal and frontal-central area (Barber et al, 2013; Shang et al, 2018; Wang et al, 2012). Previous research has revealed that the amplitude of N400 is closely associated with semantic and nonsemantic conflictions (Gunter et al, 1994; Steffensen et al, 2008).…”
mentioning
confidence: 99%
“…These components are most commonly used in neuromarketing research to measure consumer familiarity with brands and products and the conflict between price and expected value. In the reviewed literature, fourteen studies using brand-extension paradigms reported modulations in N200/N400 amplitude [ 42 , 76 , 80 , 125 , 175 , 177 , 179 , 180 , 246 , 248 , 286 , 295 , 299 , 312 ], nine studies reporting N200/N400 modulations used conflict tasks such as oddball tasks [ 79 , 81 , 97 , 100 , 107 , 126 , 129 , 205 , 259 , 311 ], and nine used other tasks, such as auction tasks or advertising stimuli [ 91 , 92 , 105 , 106 , 124 , 128 , 137 , 279 , 279 , 282 , 282 , 284 , 284 , 285 , 285 , 310 ].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Twelve out of the 15 studies which investigated brand extension in the reviewed literature found significant effects in N200 or N400 amplitude [ 76 , 80 , 125 , 177 , 179 , 180 , 246 , 248 , 286 , 297 , 299 , 312 ], while one used machine-learning and therefore did not investigate modulations in ERP amplitude directly [ 178 ]. Within the 11 studies that reported significant N200/N400 effects, nine reported significant effects of N400 amplitude [ 42 , 80 , 125 , 177 , 180 , 246 , 286 , 295 , 299 ], two reported significant N200 effects [ 76 , 179 ], while only two studies found significant effects in both N400 and N200 amplitude [ 80 , 299 ]. Further, two studies reported non-significant N2 amplitude modulations [ 297 , 299 ].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…One approach to assess this is through EEG. In addition to the measurement of electrophysiological activity response to a specific single time-locked stimulus or event as in ERP research ( Shang et al, 2018 ), longer-lasting and continuous functional indices of neural activity are also possible via EEG ( Fernandez Rojas et al, 2020 ; Firestone et al, 2020 ; Diao et al, 2021 ). Here, the EEG signal can be decomposed into various frequency spectra representing the oscillatory dynamics in the brain and correlated with certain mental processes ( Barlaam et al, 2011 ; Diao et al, 2017 ; Aoh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%